Acetylation ofWood with Various Catalysts - Çetin, Nihat Sami; Özmen, Nilgün; Birinci, Emre (ournal of Wood Chemistry and Technology, 31: 2, 142 — 153, 2011)
The purpose of this study was to compare two different acetylation mechanisms using acetic anhydride (AA) or vinyl acetate (VA) modification with using various catalysts. Acetylation of Scots pine wood flour with acetic anhydride could be significantly improved in the presence of potassium acetate, potassium carbonate, and sodium carbonate at 100◦C. Sodium carbonate had low effect on VA acetylation, potassium acetate was found to be more effective, and potassium carbonate was better for vinyl acetate modification of wood flour. The two modification methods and the effect of different catalysts on AA or VA modification were characterized by infrared and NMR spectra and analyzed in detail. The acetylation of Scots pine flour with VA and AA showed almost the same WPG values for catalysts when based on long reaction times.
Keywords: Acetic anhydride, vinyl acetate, potassium acetate, potassium carbonate, sodium carbonate